Sistem Pendidikan Jepang Studi Komparatif Perbaikan Pendidikan Indonesia - Aniswita dkk (Jurnal Dewantara, 2021)
Comparative studies of education have a strategic role in improving the quality of education of a Country. Japan as one of the countries with the best education system in the world and become a reference of other countries. Japan has advantages in its education system including the planting of character values that are integrated in the curriculum, especially for basic education. Japanese children are known for being disciplined, simple and very respectful of others. In addition, the great contribution of parents and also the community in education makes the Japanese education system very strong and quality. High public and government appreciation for teachers makes teachers have high loyalty and full commitment in carrying out their duties as educators. This certainly affects the quality of education. The best practice of Japanese education can be used as a consideration for Indonesia in developing a quality education system.